0366 Changes in Use Of Sleep Aids Following Digital Cognitive Behavioral Therapy for Insomnia. (12th April 2019) - Drake, Christopher L; Cheng, Philip; Tallent, Gabriel; Atkinson, Rachel; Cuamatzi, Andrea S; Bazan, Luisa
Abstract: Introduction: Cognitive behavioral therapy for insomnia is now recommended as first-line treatment for chronic insomnia, and can be delivered digitally (dCBT-I) for increased access. Furthermore, dCBT-I confers an advantage of reduced adverse events relative to pharmacologic interventions (e.g., hypnotics and other sleep aids). This study examined if treatment with dCBT-I can also reduce use of sleep aids compared to an online sleep education control. Methods: 1232 individuals with insomnia (DSM-5 diagnostic criteria) were randomized into two conditions: d CBT-I (N=639), or an online sleep education control (N=593). Use of medications for sleep (prescription and non-prescription) were assessed pre-treatment and post-treatment. Responses were categorized into general classes of medications (i.e. benzodiazepine, hypnotic, antihistamine, etc.), and compared across time points between the two conditions. Results: Results from a repeated-measures mixed-effects logistic regression indicated that the odds of prescription medication was significantly lower following dCBT-I compared to control (OR=0.09, 95%CI[0.02, 0.34]). Specifically, whereas prescription medication use in the control group increased from 16.5% to 18.0% at post-treatment, prescription medication use in the dCBT-I group decreased from 17.8% to 14.6%. Change in prescription medication use was more pronounced for antidepressants, followed by hypnotics. No differences were found in use of non-prescription medications. Conclusion: This study provides preliminary evidence that use of prescription sleep aids may decrease following completion of dCBT-I. Together, this suggests that a minimally resource intensive intervention may have a small effect in reducing reliance on prescription sleep aids. Support (If Any): Support for this study was provided from the National Institute of Mental Health R56MH115150 awarded to Dr. Christopher Drake.